DESIGN AN E-LEARNING COURSE UNDER A PEDAGOGICAL PERSPECTIVE - Huynh, Son Van; Le, Long Duc; Giang, Vu Thien (International Journal of Psychosocial Rehabilitation, 2020)
In the contemporary world these days, Information Technology plays a vital part in assisting teachers with their teaching and training and its combination with education is mushrooming worldwide along with various successes. The trend of using e-Learning course, which created by the utilization of technology combined with a meticulously designed teaching and training program, is one of the most notable successes. This article will go through each step of designing a simple, yet effective e-Learning course for teaching and training.